Decentralized local pricing - improving network usage in a smart-grid environment under limited information - Jessica Raasch; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
With a smart grid environment, flexible load devices and provided local price incentives a more efficient grid usage may be achieved in the future. Bidirectional communication, smart devices and shiftable loads as electric vehicles and heat pumps have the potential to be coordinated with local supply when suitable incentives are provided. This can bring relief especially for distribution grid areas where infeeds from fluctuating renewable energy sources increase. This paper presents a decentralized local pricing mechanism, aiming at local prices that reflect the current load situation. That is in case of congestion a local price, deviating from the wholesale market price, is determined. With an iterative search algorithm suitable prices can be computed without gathering full-fledged bidding data. Simultaneously self-reinforcing effects are avoided. Further on this concept can be implemented rather easily precisely where and when required so that only areas with grid congestion are affected.
Keywords: 330; Smart Grid; Real-Time Pricing; Network Pricing; Agent-Based Modeling; Price-Elastic Behavior